Precision of P/M-Parts a System Property - Vollertsen, Frank; Geiger, Manfred (Powder Metallurgy Int. 22, 1990)
It is necessary for determination of the precision of P/M parts to consider the whole system consisting of powder, the compaction press, and sintering furnace. All system parameters such as composition variations, scatter in compaction force and deviations from sintering time and temperature contribute to the final scatter in length, i.e., to dimensional accuracy. It is shown that the green density and the amount of liquid phase are the main factors determining dimensional accuracy after liquid phase sintering. The shape accuracy is primarily determined by friction forces during compaction and sintering and by the slumping effect. It is easier to control dimensional behaviour than the shape of a sintered part. A method is presented to calculate the dimensional accuracy from experimental data in order to find the critical parameters of a given system.
LFT Import::2019-08-05 (740)